Implementasi Akad Murabahah Dalam Pembiayaan Modal Usaha - Medita Pratiwi; Endeh Suhartini; Eka Suprihatiningsih (Fakultas Hukum Universitas Djuanda Bogor, 2021)
BMT Berkah Mandiri Sejahtera Cisarua Bogor is one of the Islamic financial institutions that more often uses murabahah contracts in carrying out business capital financing activities. The purpose of this study was to analyze the implementation of the murabahah contract in financing venture capital and the obstacles faced by BMT Berkah Mandiri Sejahtera Cisarua Bogor in the implementation of the murabahah contract. The method used in this study is normative juridical, with data collection carried out through reviewing data obtained in laws and regulations, books, journals, research results, observation methods, and interview methods, and then analyzing them. The results of this study are that the implementation of the murabahah contract in financing business capital at BMT Berkah Mandiri Sejahtera Cisarua Bogor is still not fully in accordance with the DSN-MUI Fatwa Number 4 of 2000 concerning Murabahah and the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 11 of 2017 concerning the Implementation of Business Activities. Savings and Loans and Sharia Financing by Cooperatives. Then the obstacle in implementing the murabahah contract at BMT Berkah Mandiri Sejahtera comes from the lack of understanding of the murabahah contract itself, both from the community and the BMT